The Influence Of Customer Satisfaction On Customer Loyalty Of Roemah Merdeka Palembang - Salim, Rizko Saputra; Megawati , Megawati (Jurnal Multidisiplin Sahombu, 2025)
This study aims to analyze the Influence of Promotion, Service Quality, Customer Satisfaction, and Trust on Customer Loyalty of Roemah Merdeka Palembang This study uses a descriptive quantitative method and with a sample of 398 respondents. The data analysis method used non-probability sampling, purposive sampling, and multiple regression with the SPSS version 25 test tool. Based on the results of the study, it shows that the variables of Customer Satisfaction have a significant and positive effect partially or simultaneously on the Customer Loyalty of Roemah Merdeka Palembang